Melanotic neuroectodermal tumor of infancy: case report Tumor melanótico neuro-ectodérmico da Infância: relato de caso - Ápio Cláudio Martins Antunes; Rodrigo Maciel Freitas; Patrícia P. Oliveira; Ricardo G. Rebouças (Arquivos de Neuro-Psiquiatria)
INTRODUCTION: Melanotic neuroectodermal tumor of infancy (MNTI) is a rare tumor, locally aggressive, usually originated from maxilla and mandible and rarely from the skull. A case of a 4 month-old child presenting a bulging lesion in the midline of the occipitoparietal region with progressive growth is reported. CASE REPORT: The neurologic examination had normal developmental milestones. Computerized tomography scan and magnetic resonance Image showed a highly enhancing tumor, dislocating anteriorly and inferiorly the superior sinuses. In order to prevent excessive bleeding, surgical resection was performed in three stages, with complete removal. CONCLUSION: Based on the absence of tumor recurrence, we believe in a favorable neurological prognosis and in a possible of cure, although the patient was not submitted to any adjuvant treatment. O tumor melanótico neuro-ectodérmico da infância é raro, localmente agressivo, originado da maxila ou da mandíbula, raramente originando-se da calota craniana. Relatamos o caso de um menino de 4 meses de idade que apresentava lesão abaulada com crescimento progressivo no couro cabeludo. O exame neurológico apresentava desenvolvimento neuro-psicomotor adequado. A tomografia computadorizada e a ressonância magnética do encéfalo mostravam lesão que impregnava pelo contraste, deslocando anterior e inferiormente o seio sagital superior. Com o objetivo de prevenir o risco do sangramento excessivo, o procedimento foi realizado em três tempos, com remoção completa da lesão. Baseados na ausência de recidiva do tumor, acreditamos no bom prognóstico neurológico e na possibilidade de cura, embora o paciente não tenha sido submetido a nenhum tratamento adjuvante.